Payment of Judgments and Conciliations of the Ministry of National Defense in 2022 (2024)
In this essay a description of the procedure carried out within the Ministry of National Defense (MDN hereinafter) in 2022, for the payment of judgments and conciliations charged to the Public Debt of the Nation, the administrative, legal, financial and human talent capacity provided by the National Government is mentioned, the Ministry of Finance and Public Credit (MHCP hereinafter), the MDN and other entities involved to meet one of the objectives proposed in the National Development Plan, Law 1955 of 2019 “Whereby the National Development Plan 2018-2022 pact for Colombia, pact for Equity is issued. “achieving historical payments for a value exceeding three trillion six hundred billion pesos, the additional burden generated by the monetary value in the Public Budget of the Nation, the incidences when assuming the payment charged to the Public Debt item, the additional burden of payment at the time of recognizing the default interest of the enforced orders originated by the long lines of time to make the disbursement of the expenditure that, The long time lines for the disbursement of the expense, which are normally assumed by the Judgments item associated to operating expenses and due to its low allocation in comparison with the volume of claims against the Nation - Ministry of National Defense, caused a scenario of uncertainty in which the administration is limited to comply in a timely manner with the payment of the obligations. Finally, a brief comparison is made in relation to the budgetary allocations made in the Appropriations Law in comparison with the payments to be made by the MDN until 2031, with the purpose of honoring the Nation's Debt.